Learning Method of Ta'limul Muta’allim Book in Forming Character and Improving Students' Learning Achievement: Metode Pembelajaran Kitab Ta’limul Muta’allim dalam Pembentukan Karakter dan Meningkatkan Prestasi Belajar Santri - Syirotun Nadiyah Agustin; Devy Habibi Muhammad (Halaqa: Islamic Education Journal, 2020)
The focus of this study are: 1) How the learning methods of Ta'limul Muta'allim books in character formation, 2) How are the learning methods of Ta'limul Muta Books 'allim in improving student learning achievement, 3) What are the obstacles faced and how are the solutions. The purpose of this study are: 1) To find out how the learning methods of the Ta'limul Muta'allim book in character formation, 2) To find out the learning methods of the Ta'limul Muta'allim Book in improving student achievement, 3) To find out what are the obstacles faced and how the solution. The method used in this study uses qualitative research methods, in the process the researcher uses interview, observation, and doc- umentation techniques. From the results of this study, it can be concluded that learning Ta'limul Muta'allim in character formation using qira'ah and demonstration methods can help students read to better understand the subject matter, then after being explained students practice the results of what is explained and understood.